2020
DOI: 10.1007/s42835-020-00430-9
|View full text |Cite|
|
Sign up to set email alerts
|

Failure Diagnosis Method of Photovoltaic Generator Using Support Vector Machine

Abstract: The capacity of photovoltaic (PV) generators can increase owing to the 4030 policy of the Government of South Korea.. In addition, there has been significant interest in developing a technology for the maintenance of PV generators owing to an increase in the number of outdated PV generators. This paper describes a failure diagnosis method that uses operational data for power generation and solar radiation of PV generators. The measured data stored since four years in an operational 50-kW PV generator that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Many ML-based fault/defect detection [ 333 , 334 , 335 , 336 , 337 , 338 ] and quality monitoring approaches [ 336 ] have been proposed in the literature. Several examples of fault diagnostics [ 335 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 ] are also available in the literature. Bayesian approaches that enable root cause analysis of quality issues [ 350 , 351 ] have also been proposed.…”
Section: Key Building Blocks Technology Enablers and Innovation Accel...mentioning
confidence: 99%
“…Many ML-based fault/defect detection [ 333 , 334 , 335 , 336 , 337 , 338 ] and quality monitoring approaches [ 336 ] have been proposed in the literature. Several examples of fault diagnostics [ 335 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 ] are also available in the literature. Bayesian approaches that enable root cause analysis of quality issues [ 350 , 351 ] have also been proposed.…”
Section: Key Building Blocks Technology Enablers and Innovation Accel...mentioning
confidence: 99%
“…Experimental results showed that this model is superior to other traditional models. In literature [32], SVM was used as a fault diagnosis model to distinguish the normal and fault state of PV generating sets, and relevant data was used to conduct experiments. The results showed that this method could better realize the fault diagnosis of PV generating sets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both simulation and experimental results show that the method is effective for PV array fault diagnosis [18]. Cho et al proposed a fault diagnosis method based on support vector machine classification to perform the fault diagnosis of PV generators using real operation data [19]. Adhya et al examined the effectiveness of categorical boosting, light gradient boosting and extreme gradient boosting methods for PV array fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%